2014
DOI: 10.1175/jpo-d-12-0237.1
|View full text |Cite
|
Sign up to set email alerts
|

Wave Breaking Dissipation in a Young Wind Sea

Abstract: Coupled in situ and remote sensing measurements of young, strongly forced wind waves are applied to assess the role of breaking in an evolving wave field. In situ measurements of turbulent energy dissipation from wave-following Surface Wave Instrument Float with Tracking (SWIFT) drifters and a tethered acoustic Doppler sonar system are consistent with wave evolution and wind input (as estimated using the radiative transfer equation). The Phillips breaking crest distribution Λ(c) is calculated using stabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 58 publications
4
63
1
Order By: Relevance
“…Measured distributions of breaking rate show a peak at a phase speed approximately half that of the spectral peak with dissipation of high-frequency, short waves composing a significant fraction of the total breaking rate (Gemmrich et al 2008;Thomson et al 2009;Schwendeman et al 2014). Schwendeman et al (2014) also noted that a regime shift occurs in young wind seas where large whitecaps replace, not add to, small-scale breakers as forcing becomes stronger. Furthermore, field observations of the dissipation of turbulent kinetic energy (TKE) beneath surface gravity waves exceed wallbounded shear flow scaling (Kitaigorodskii et al 1983;Agrawal et al 1992;Drennan et al 1992;Terray et al 1996;Drennan et al 1996,;Gemmrich and Farmer 1999,;Gemmrich 2010;Scully et al 2016).…”
Section: Wave-enhanced Turbulent Mixingmentioning
confidence: 91%
See 1 more Smart Citation
“…Measured distributions of breaking rate show a peak at a phase speed approximately half that of the spectral peak with dissipation of high-frequency, short waves composing a significant fraction of the total breaking rate (Gemmrich et al 2008;Thomson et al 2009;Schwendeman et al 2014). Schwendeman et al (2014) also noted that a regime shift occurs in young wind seas where large whitecaps replace, not add to, small-scale breakers as forcing becomes stronger. Furthermore, field observations of the dissipation of turbulent kinetic energy (TKE) beneath surface gravity waves exceed wallbounded shear flow scaling (Kitaigorodskii et al 1983;Agrawal et al 1992;Drennan et al 1992;Terray et al 1996;Drennan et al 1996,;Gemmrich and Farmer 1999,;Gemmrich 2010;Scully et al 2016).…”
Section: Wave-enhanced Turbulent Mixingmentioning
confidence: 91%
“…Wave breaking in deep water is the result of wind-wave, wave-wave, and wave-current interactions (Melville 1996). Measured distributions of breaking rate show a peak at a phase speed approximately half that of the spectral peak with dissipation of high-frequency, short waves composing a significant fraction of the total breaking rate (Gemmrich et al 2008;Thomson et al 2009;Schwendeman et al 2014). Schwendeman et al (2014) also noted that a regime shift occurs in young wind seas where large whitecaps replace, not add to, small-scale breakers as forcing becomes stronger.…”
Section: Wave-enhanced Turbulent Mixingmentioning
confidence: 99%
“…Although some of the available estimates of the non-dimensional breaking strength parameter, b, in the field (Thomson, Gemmrich & Jessup 2009;Schwendeman et al 2014) are comparable to those in spillers due to dispersive energy focusing (Drazen et al 2008;Tian et al 2010), most of the field estimations of b (Phillips, Posner & Hansen 2001;Gemmrich, Banner & Garrett 2008;Gemmrich et al 2013) tend to be more consistent with the observed b values in weak spillers due to modulational instability (Banner & Peirson 2007;Allis 2013). Here, we briefly establish that the present model is capable of capturing breaking waves due to modulational instability.…”
mentioning
confidence: 98%
“…Beside dispersive energy focusing, other mechanisms such as modulational instability (Benjamin & Feir 1967;Melville 1982) and wind forcing (Grare et al 2013;Schwendeman, Thomson & Gemmrich 2014) can induce wave breaking. Although some of the available estimates of the non-dimensional breaking strength parameter, b, in the field (Thomson, Gemmrich & Jessup 2009;Schwendeman et al 2014) are comparable to those in spillers due to dispersive energy focusing (Drazen et al 2008;Tian et al 2010), most of the field estimations of b (Phillips, Posner & Hansen 2001;Gemmrich, Banner & Garrett 2008;Gemmrich et al 2013) tend to be more consistent with the observed b values in weak spillers due to modulational instability (Banner & Peirson 2007;Allis 2013).…”
mentioning
confidence: 99%
“…In Melville (2010, 2011) and Romero et al (2012), an IMU was used to gather the positional data needed to rectify images taken from an airborne system. In Schwendeman et al (2014), a shipboard camera was actively stabilized with an inertial pan-tilt system. There are two disadvantages of this strategy.…”
Section: Introductionmentioning
confidence: 99%